EFFECTIVENESS OF PPKM (ENFORCEMENT OF RESTRICTIONS ON COMMUNITY ACTIVITIES) EMERGENCY AND LEVELS 1-4 ON CONTROL OF SPREAD COVID 19 VIRUS IN EAST JAVA - Taufiq Rahman Ilyas (PERCIPIENCE International Journal of Social, Administration, & Entrepreneurship, 2021)
The second wave of the covid 19 virus pandemic which is getting out of control has made the Government move quickly and respond to an emergency as a strategic step in suppressing the rate of transmission of the covid 19 virus. Through the PPKM (Enforcement of Community Activity Restrictions) policy as an effort to control the covid 19 virus pandemic, it is a preventive measure in suppressing the spread of the COVID-19 pandemic. The rate of increase in Covid-19 cases in East Java. The three weeks that lasted from the emergency PPKM (Enforcement of Community Activity Restrictions) to PPKM (Enforcement of Community Activity Restrictions) levels 1 to 4 have shown significant numbers in controlling the spread of COVID-19 cases in East Java with a decrease in the percentage of cases and a decrease in the number of transmissions and an increase. the number of cure rates of the exposed population